Discours, agro-industrie et le silenciement des femmes dans la production de café au Brésil - Mónica Graciela Zoppi-Fontana; Sheilla Maria Resende (Les Cahiers ALHIM)
This article presents a research on the silencing process produced by the agrobusiness on women coffee producers in the southern region of Minas Gerais, Brazil. Starting from the hypothesis that the silences produced by the agrobusiness institutional discourse could be described, an analysis of a mixed corpus was made: on one side, the discourse of the agrobusiness, on the other side, the discourse of women coffee growers. The theoretical approach for this research is that of Discourse Analysis, in specific the research of Michel Pêcheux (1975; 1990) and Eni Orlandi (2000), through the mobilization of the following theoretical-analytical categories: silencing, silence, form-subject, memory. The results provide a description of the syntactic and semantic operations that make it possible to actualize and put into operation a patriarchal memory of agricultural practice, which silences both the role of women in the coffee production chain and family agriculture.